Frontiers of the Roman empire the Roman frontier in Georgia - Karasiewicz-Szczypiorski, Radosław; Mamulaje, Šot̕a 1952-2024; Breeze, David J. 1944- (Archaeopress, 2024)
An accessible summary of the history of the Roman Frontier in Georgia, placed into its wider context by a supporting essay from David Breeze looking at the whole Roman Frontier as an interconnected world heritage site. From the times of Pompeius Magnus to the period of the Persian Wars of Justinian I the Great, Roman military expeditions passed through Colchis and Iberia many times. However, the Roman Empire never permanently conquered the territory of Georgia. For this reason, diplomatic relations were also maintained with the local rulers, especially the kings of Iberia. The first centuries AD were a time of intense cultural exchange (through diplomacy and trade) between the southern Caucasus and the eastern provinces of the Roman Empire. Traces of these relations include valuable artefacts, found in elite burials and deposits, which we can see today in the Batumi Archaeological Museum, among others. This is no coincidence, as local communities living on the Black Sea coast from Trebizond to the Caucasus had particularly close relations with the Romans. These areas were also home to garrisons subordinate to the governor of the Roman province of Cappadocia.